2020
DOI: 10.3390/molecules25112507
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Reactive-Dye Chromophores and DEG on Ink-Jet Printing Performance

Abstract: Digital inkjet printing has been widely used in textile industry. The quality of dye solutions and ink-jet droplets limits the ink-jet printing performance, which is very important for obtaining high-quality ink-jet printing images on fabrics. In this paper, we introduced diethylene glycol (DEG) into the dye solutions of Reactive Blue 49 and Reactive Orange 13, respectively, and investigated the interaction between dye chromophores and DEG molecules. Results indicated that the dye chromophores were featured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Visible absorption spectroscopy is an important technique to investigate the stability, water solubility, and application properties of dye molecules. , In this study, visible absorption spectra were recorded to study the interactions between additives and dye molecules, which can help us in understanding the microbehavior of surface tension and viscosity of different prepared inks. The visible absorption spectra of PEG-dye and PEG-S465-dye inks were recorded and plotted as shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Visible absorption spectroscopy is an important technique to investigate the stability, water solubility, and application properties of dye molecules. , In this study, visible absorption spectra were recorded to study the interactions between additives and dye molecules, which can help us in understanding the microbehavior of surface tension and viscosity of different prepared inks. The visible absorption spectra of PEG-dye and PEG-S465-dye inks were recorded and plotted as shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chen et al 24 prepared a recording layer with SiO 2 @Al 13 core‐shell composite, the smoothness, glossiness and printing image of the recording layer were better than the layer with SiO 2 , and the performance and the clarity of the image had also improved as shown Figure 7(b). Zhang et al 89 introduced diethylene glycol (DEG) into the dye solution of Blue 49 and Orange 13. The results indicated that the addition of the DEG could eliminate satellite ink droplets, and improve the resolution of the image printing quality as shown Figure 8.…”
Section: Performance Evaluation Systemsmentioning
confidence: 99%
“…Ink‐jet ink droplet spreading and printed images: (a)–(d) 120 mmol/L reactive blue 49 solutions with different concentrations of DEG: (a) 0, (b) 1, (c) 2, and (d) 3 mol/L. (a′)–(d′) corresponding photos of cotton fabrics treated by reactive Orange 13 from (a)–(d); (e), (f) 120 mmol/L reactive Orange 13 dye solutions with different concentrations of DEG (e), (f): (e) 0, (f) 1, (g) 2, and (h) 3 Mol/L; (e′)–(h′) corresponding photos of cotton fabrics treated by reactive blue 49 from (e), (f) (reproduced from Reference 88 with permission from [MDPI]) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Performance Evaluation Systemsmentioning
confidence: 99%
“…Therefore, it's a huge potential that enterprises effectively improve the utilization rate of high concentration dyes based on this nonaqueous system to save costs and create more pro ts. But the reactive dyes aggregate easily at a high concentration (Egabaierdi et al 2022;Zhang et al 2020), which will reduce their diffusion rate from the surface of ber to the interior. Additionally, although there are many hydroxyl groups in cellulose bers, the nucleophilic substitution or addition reaction between dye and hydroxyl groups mainly occurs in the amorphous region of cellulose (Cai et al 2020).…”
Section: Introductionmentioning
confidence: 99%